A Morphological Study of Affixes Used by Major and Minor Characters in the Novel Through the Looking Glass - Puspita Dewi (Pioneer: Journal of Language and Literature, 2019)
This research is entitled A Morphological Study of Affixes Used by Major and Minor Characters in the Novel Through the Looking Glass. The objectives of this research are to identify the affixes, to find out the derivation and inflection changes used by characters in the novel Through the Looking Glass and to find out the most dominant affixes. The method of this research is qualitative research. The results of this research are: (1) affixes found at major characters are suffix, prefix, and confix. Afterward, affixes found at minor characters are suffix and prefix, (2) this research found 40 derivations and 85 inflection used by major characters. Besides, this research found six derivations and 17 inflections used by minor characters, and (3) the most dominant affix found at characters are suffix. In total of suffixes used by major character, there were 31 –ing, 10 –ly, 42 –s, 3 –y, 3 –able, 2 –ation, - -d, 15 –ed, 4 –er, 3 –es, 1-est, 2 –ful, 1 –ination, 1 –ish, 3 –ment, 1 –ness, 1 –or, 1 –ous, 1 –t, and 1 -th. Afterward, suffix found at minor characters there were 1 –ance, 4 –ing, 2 –es, 10 –s, 1 –ly, and 1 –ed.